2020
DOI: 10.7759/cureus.6599
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Body Stature Using the Percutaneous Length of Ulna of an Individual

Abstract: To explore the association between the percutaneous length of ulna and height of that individual and to formulate a gender-specific formula. Methods This is a cross-sectional study conducted at the Nishtar Medical University, Multan from May 1 2019 to July 1 2019. Length of ulna and body height were measured for 100 participants, including an equal number of males and females. Means of age, length of ulna and body height were compared between both genders. Regression coefficient, Pearson correlation coefficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 20 publications
1
7
0
1
Order By: Relevance
“…Previous studies showed that forearm length was well correlated with height [24,30]. Forearm length was used as an alternative to height in elderly patients [31].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that forearm length was well correlated with height [24,30]. Forearm length was used as an alternative to height in elderly patients [31].…”
Section: Discussionmentioning
confidence: 99%
“…The current finding of high correlation when using ulna length as a surrogate height measure is consistent with other international studies. These studies have analysed a wide age range and in a variety of populations: infants, 7 adolescents, 3,[23][24][25][26] adults 20,22 and older adults. 16 All of these populations found a linear relationship between height and ulna length.…”
Section: Discussionmentioning
confidence: 99%
“…7,15,16 Furthermore, it has greater precision than the lower limbs in formulating a regression equation. 18 Ulna length has also been shown to have high reliability and correlation with height in several adult studies, 15,[19][20][21][22] although only a few studies have assessed this in adolescents. 3,[23][24][25][26] From these, only four studies provided equations from which to estimate height.…”
Section: Introductionmentioning
confidence: 99%
“…Patient’s height showed a weaker correlation with CC field length and this could be explained by a change in patient height not being in proportion to a change in the patient’s neck length. Other clinically measurable anthropometric factors such as the percutaneous lengths of the ulna 13 and tibia 14 have been reported to be predictors of a patient’s stature. However, these measurements were not readily available for correlation with the CC field length and this analysis was beyond the scope of this study.…”
Section: Discussionmentioning
confidence: 99%